Studies on Echocardiographic Assessment of Healthy Non Descript Dogs - Kunjadiya, Rajan J; Patel, Manish D; Parmar, Saurabh M; Mehta, Sudhir A; Vala, Jignesh A. (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Considering echocardiography as the most widely accepted non-invasive diagnostic tool for assessing cardiac anatomy and function in small animals, present study was planned to assess echocardiographic parameters in dogs. Total 18 clinically healthy non-descript dogs were subjected to 2-D and M-mode echocardiographic examinations. Dogs were categorized by gender, age and body weight to assess their effects on various echocardiographic parameters. The mean LA, Ao, and LA/Ao ratio values were 1.70±0.04 cm, 1.72±0.05 cm, and 1.00±0.03, respectively, with non-significant group differences. However, the mean LA/Ao ratio was higher in dogs weighing >20 kg (1.04±0.03) compared to those <20 kg (0.91±0.04). M-mode echocardiographic parameters were within normal limits. Gender and body weight differences were non-significant, but age-related differences were observed. Dogs >3 years had significantly higher mean values of EF (69.05±3.84%), FS (38.34±3.31%), and CO (1991.34±201.95 mL/min) compared to those <3 years (51.92±6.11%, 25.97±3.65%, and 1330.71±213.40 mL/min, respectively). Other M-mode parameters varied non-significantly across age groups. The study concludes that the variation in certain echocardiographic parameters should be taken into consideration while evaluation of cardiac diseases in non-descript dogs.